Factors Influencing EFL Pre-service Teachers’ Experience in Classroom Management - Waloyo, Edy; Rifai, Ahmad; Tanjung, Khoiriyah Shofiyah; Mutiaraningrum, Ira (Institut Agama Islam Negeri Kudus, 2023)
Classroom management has been of interest for decades. EFL Pre-service teachers at IAIN Syekh Nurjati Cirebon had experiences in teaching practices and classroom management. They had completed teaching practices at formal school for two months. This quantitative research employed factor analysis to determine the research variables that affect classroom management. The variables of classroom management involved in this study are discipline, organization of the lesson, interaction during the lesson, teacher-student personal communication, and psychological and social classroom environment. The findings show that the KMO Measure of Sampling Adequacy (MSA) number is 0.800. Because the value is 0.800 (> 0.5), it means that all factors influence EFL pre-service teachers’ experience in classroom management. This study highlights discipline as the main factors contributing to classroom management. This study also highlights the role of the university in preparing pre-service teachers to be ready for their future teaching practice.